Simulador para el Control financiero de las Pymes - Méndez Giraldo, Germán Andrés; Parra, Patricia; Hurtado Portela, Jose (Ingeniería, 2008)
In year 2004 was finished the investigation about Prototype Design of Diagnosis for the SMEs, after that, the work was continuing in order to develop new opportunities to be better at these industries. The present article shows a result derived from this work and that based on the methodology developed by the group of investigation SES. For it a mental model was elaborated that gave rise to a simulation model with which it is allowed to identify tendencies to the interior of the system, which does possible to realise projections of the financial system for SMEs. Between the main variables of influence they are the liquidity, the work capital, the investments (tangible and intangible), the management and control of budgets, the yield and the financing (internal or external). Also, It considers a model of continuous simulation to reflect the policies that define the decisions to the interior of the area, the fundamental profile of the maanger and other variables and parameters in the analysis of the financial management. One concluded after realising the different scenarios from simulation that the main financial problems of the SMEs not only are related to the external credit, as traditionally it is created, also has a strong influence the internal structure and the enterprise culture, because the decisions are taken according to the vision of the industralist and few have brings back to consciousness to invest in the improvement of the company.